Clinical utility of progranulin in patients with systemic lupus erythematosus - Reem M Ibrahem; Khalida E ElRefaie; Sally S Abd Elhamed; Eman M.S Elbagoury (Wolters Kluwer Medknow Publications, 2020)
Background Systemic lupus erythematosus (SLE) is a systemic autoimmune disease. SLE has different presentations that are not specific to the disease itself. Diagnosis and assessment of disease activity are considered a challenge to patients and physician, as both need experienced clinician to evaluate symptoms and laboratory findings. So, it is very important to search for an accurate diagnostic marker for SLE activity. In the past few years, increasing evidence has shown that progranulin (PGRN) may play a role in regulation of adaptive and innate immunity, so it might be a marker for disease activity. Aim To investigate the clinical significance of PGRN in patients with SLE regarding its role in pathogenesis and its correlation to clinical manifestations and disease activity. Patients and methods This is a case-control study conducted on 96 participants. Group I included 56 patients with SLE subdivided according to SLE Disease Activity Index (SLEDAI) score into patients with active and inactive SLE. Group II included 40 apparently healthy volunteers as a control group. All patients were subjected to a thorough history; complete clinical examination; assessment of disease activity by using SLEDAI; and laboratory investigations, including complete blood count, liver function, kidney function, complete urine analysis, anti-nuclear antibody, anti-double-stranded DNA antibody, complement 3, complement 4, and serum PGRN. Results There was a highly statistically significant increase in serum PGRN level in patients with SLE compared with healthy control group. Moreover, a positive correlation was found between PGRN levels and SLEDAI score. Conclusion Patients with SLE with higher SLEDAI score have higher serum PGRN level. So, serum PGRN level might play a role in SLE pathogenesis and as diagnostic marker for SLE activity.